Effectiveness of a School-Based Intervention on the Students’ Mental Health After Exposure to War-Related Trauma - El-Khodary, Basel; Samara, Muthanna (Frontiers in Psychiatry, 2020)
Background After the war, which was conducted against Palestinian civilians in the Gaza Strip, the prevalence of posttraumatic stress disorder (PTSD) among children and adolescents has increased. The counselling department at the Ministry of Education in the Gaza Strip applied a counselling program in schools in order to alleviate the effect of exposure to war. The aim of the study is to investigate the effectiveness of the counselling program after exposure to war-traumatic events among Palestinian children and adolescents in the Gaza Strip. Methods The sample consists of 572 students aged 12–18 years old. Of them, 331 (57.9%) were female and 241 (42.1%) were male. Traumatic events were measured by War-Traumatic Events Checklist (W-TECh). PTSD was measured by the Post-Traumatic Stress Disorders Symptoms Scale (PTSDSS). Anxiety symptoms were adapted from The Anxiety Symptoms Scale, and depression symptoms were measured by Child Depression Inventory. Repeated measures design was employed as the counselling program was applied in all the schools at the same time. Specifically, the data were collected from the participants before the application of the counselling program and 2 months later. Results After applying the school-based counselling program, the prevalence of PTSD (according to DSM-V) decreased from 57.5% to 45.6% among the children and adolescents who were exposed to war-traumatic events. In addition, PTSD symptoms, and emotional, somatic and cognitive functional impairment symptoms has decreased after the implementation of the counselling program especially amongst girls. Conclusions The school-based counselling program was effective in decreasing the PTSD symptoms among children and adolescents after the exposure to war-traumatic events.